Corticostriatal Field Potentials Are Modulated at Delta and Theta Frequencies during Interval-Timing Task in Rodents - Emmons, Eric B.; Ruggiero, Rafael N.; Kelley, Ryan M.; Parker, Krystal L.; Narayanan, Nandakumar S. (Frontiers in Psychology, 2016)
Organizing movements in time is a critical and highly conserved feature of mammalian behavior. Temporal control of action requires corticostriatal networks. We investigate these networks in rodents using a two-interval timing task while recording local field potentials in medial frontal cortex or dorsomedial striatum. Consistent with prior work, we found cue-triggered delta (1-4 Hz) and theta activity (4-8 Hz) primarily in rodent medial frontal cortex. We observed delta activity across temporal intervals in medial frontal cortex and dorsomedial striatum. Rewarded responses were associated with increased delta activity in medial frontal cortex. Activity in theta bands in medial frontal cortex and delta bands in the striatum was linked with the timing of responses. These data suggest both delta and theta activity in frontostriatal networks are modulated during interval timing and that activity in these bands may be involved in the temporal control of action.